Highly Efficient Transfer Hydrogenation Catalysis with Tailored Pyridylidene Amide Pincer Ruthenium Complexes. Issue 58 (17th September 2020) - Melle, Philipp; Thiede, Jan; Hey, Daniela A.; Albrecht, Martin
Abstract: The rational optimization of homogeneous catalysts requires ligand platforms that are easily tailored to improve catalytic performance. Here, it is demonstrated that pyridylidene amides (PYAs) provide such a platform to custom‐shape transfer hydrogenation catalysts with exceptional activity. Specifically, a series of meta ‐PYA pincer ligands with differently substituted PYA units has been synthezised and coordinated to ruthenium(II) centres to form bench‐stable tris ‐acetonitrile complexes [Ru(R‐PYA‐pincer)(MeCN)3 ](PF6 )2 (R=OMe, Me, H, Cl, CF3 ). Analytic studies including 1 H NMR spectroscopy, cyclic voltammetry, and X‐ray crystallography reveal a direct influence of the substituents on the electronic properties of the ruthenium center. The complexes are active in the catalytic transfer hydrogenation of ketones, with activities directly encoded by the PYA substitution pattern. Their perfomance improves further upon exchange of an ancillary MeCN ligand with PPh3 . While complexes [Ru(R‐PYA‐pincer)(PPh3 )(MeCN)2 ](PF6 )2 were only isolated for R=H, Me, an in situ protocol was developed to generate these complexes in situ for R=OMe, Cl, CF3 by using a 1:2 ratio of the complexes and PPh3 . This in situ protocol together with a short catalyst pre‐activation provided highly active catalytic systems. The most active pre‐catalyst featured the methoxy‐substituted PYA ligand and reached turnover frenquencies of 210 000 h −1 under an exceptionally low catalyst loading of 25 ppm for the benchmark substrate benzophenone, representing one of the most active transfer hydrogenation systems known to date. Abstract : The rational optimization of homogeneous catalysts requires ligand platforms that are easily tailored to improve catalytic performance. Here, it is demonstrated that pyridylidene amides (PYAs) provide such a platform to custom‐shape transfer hydrogenation catalysts with exceptional activity.The complexes are active in the catalytic transfer hydrogenation of ketones, with activities directly encoded by the PYA substitution pattern.